Central pain processing does not differ between first episode and recurrent acute low back pain. - Chang, Wei-Ju; Buscemi, Valentina; Liston, Matthew B.; McAuley, James H.; Schabrun, Siobhan M. (Physiotherapy Practice & Research, 2020)
BACKGROUND: One-third of individuals with acute low back pain (LBP) experience recurrent symptoms within 12 months but the underlying mechanisms are unclear. One explanation is that individuals experiencing recurrent LBP develop altered central pain processing that predisposes to symptom recurrence. We compared central pain processing between individuals experiencing their first episode of acute LBP, recurrent acute LBP, and pain-free controls. METHODS: A cross-sectional study was conducted to evaluate central pain processing in 11 individuals experiencing their first episode of acute LBP, 11 individuals with recurrent acute LBP, and 11 pain-free controls. Outcome measures included pain and disability, pressure and heat pain thresholds (PPTs and HPTs), nociceptive flexor withdraw reflex (NFR) and conditioned pain modulation (CPM). RESULTS: The NFR latency was shorter in individuals experiencing their first episode of acute LBP when compared with pain-free controls (p = 0.01). Descending inhibitory pain control measured by CPM was less efficient in both acute LBP groups when compared with pain-free controls. HPTs and PPTs did not differ between people with and without acute LBP. There were no differences between the two LBP groups for any outcome measure. CONCLUSIONS: These data demonstrate altered central pain processing in the acute stage of LBP. However, the degree of impairment did not differ between individuals with a first episode vs. recurrent acute LBP. These findings suggest that altered central pain processing in acute LBP is not related to a previous history of LBP.